Nonlinear impulsive Volterra integral equations in Banach spaces and applications. (1993) - Guo Guo, Dajun Dajun
Abstract : In this paper, we first extend results on the existence of maximal solutions for nonlinear Volterra integral equations in Banach spaces to impulsive Volterra integral equations. Then, we give some applications to initial value problems for first order impulsive differential equations in Banach spaces. The results are demonstrated by means of an example of an infinite system for impulsive differential equations.